A herd immunity to measles and rubella viruses in the population of the Republic of Serbia - M. A. Bichurina (Sankt-Peterburg : NIIÈM imeni Pastera, 2021)
According to the WHO Strategic Plan, measles should be eradicated in 2020 in the five WHO Regions including European Region. However, large measles outbreaks are being periodically registered in diverse European countries. In the Republic of Serbia (SRB), 5,076 measles cases were detected in 2018, among which 15 cases were fatal.Aim of the study was to examine herd immunity to measles and rubella viruses in the population of the Republic of Serbia.Materials and methods. Blood serum samples obtained in 2018 and 2019 from conditionally healthy residents of the Republic of Serbia were tested for the presence of IgG antibodies to measles and rubella viruses in five age groups: I — children from 2 to 6 years old, II — children from 8 to 14 years old, III — 15 to 24 years old, IV — 25 to 49 years old and V — over 50 years old. A total of 1000 samples were obtained, 200 sera in each group. Enzygnost® Anti-Measles virus/IgG and Enzygnost® Anti-Rubella virus/IgG ELISA test systems (Siemens Healthcare Diagnostics Products GmbH, Germany) were used according to the manufacturer's instructions.Results. Overall, around 23.0% and 33.7% of the surveyed persons had no or low level of anti-measles IgG antibody (≥ 275.0 — ≤ 1000.0 IU/1). In age group I, 60% children contained no or “low” anti-measles antibodies titer (29.5% and 30.5%, respectively). In addition, low antibody titer level was mainly detected in individuals from age group II and III (p < 0.05). A third of children under 8—14 contained high IgG-antibodies titer against measles (> 3000.0 IU/l) that might serve as an evidence that such subjects recently recovered after measles. Similar results were obtained for IgG antibodies to rubella in the same age groups.Discussion. The study results evidence about altered routine immunization against measles and rubella in children aged 12—15 months (first vaccination) and those at age of 6—7 years (revaccination) with MMR vaccine. The data obtained correlate with official data on coverage with measles and rubella vaccines in the Republic of Serbia.